Development, demographic transition and net migration: evidence for the municipalities of Mexico, 2000-2010 - Peláez-Herreros, Óscar (Iberoamerican Journal of Development Studies, 2013)
In this paper we review and integrate into a single analytical framework the theoretical approaches that explain the connection of the development process with natural population growth, migration and income inequality. Also, we provide evidence of the direction and intensity of these relations for the case of Mexico. With this purpose, we estimate the net migration rate of the 2,443 municipalities of the country during the period 2000-2010, finding that higher levels of development correspond to lower rates of natural population growth and with lower rates of emigration. We find no evidence of a hypothetical positive relationship between emigration and inequality, and doubt about that income inequality increases at the beginning of the development process and then decline. In any case, the detected relationships are weak, suggesting that some specific factors are left out of the analysis.